Case report: A case of heterogeneity of the antitumor response to immune checkpoint inhibitors in a patient with relapsed hepatocellular carcinoma - Bao, Yingying; Wen, Liang; Chen, Wen; Zhao, Jianhui; Yang, Yixiao; Wei, Tao; Zhang, Jian; Liang, Tingbo (Frontiers in Oncology, 2022)
The existence of tumor heterogeneity is widely recognized; however, heterogeneity of the antitumor response in multiple tumor nodules in the same patient has not been reported. Sintilimab, a monoclonal antiprogrammed cell death receptor-1 (PD-1) antibody, was used to treat patients with unresectable hepatocellular carcinoma (HCC). In the present study, we report a case of therapeutic heterogeneity in relapsed HCC with lung metastases. A 57-year-old female patient was diagnosed with HCC and underwent radical hepatectomy. One and a half years later, imaging scans found multiple metastatic tumors in the lung, which were accompanied by an increased α-fetoprotein (AFP) level. The patient then started to receive sintilimab. In the first 6 months after sintilimab treatment, all the metastatic nodules regressed gradually and ultimately disappeared, except for one nodule, which remained stable in the following 3 months. Finally, the patient underwent pulmonary lobectomy to remove the remaining nodule. Thereafter, follow-up visits showed the AFP level decreased to normal and imaging scans showed no signs of recurrence, confirming that the patient exhibited a clinically complete response. Pathological assessments showed that in the primary tumor site, the tumor comprised moderately differentiated HCC with a few infiltrated cytotoxic T cells and negative PD-L1 expression. While in the metastatic site, the nodule was composed of poorly differentiated HCC with cytotoxic T-cell infiltration with few cells inside the tumor and expressed PD-L1 in some areas of the tumor. There were dynamic alterations of PD-L1 expression and cytotoxic T-cell infiltration in the primary and relapsed HCC lesions after anti-PD-1 treatment. This case presented the heterogeneities of both the tumor microenvironment and the following antitumor response among the metastatic nodules in the same patient and revealed the importance of comprehensive therapy in cancer treatment.